Variability, Traits Association And Path Coefficient Of Yield And Yield Contributing Traits Of Selected Boro Rice (Oryza Sativa L.) Germplasm (SAARC Journal of Agriculture, 2020)
Boro season is the most productive among Aus, Aman and Boro seasons. For confirming food security, we need to emphasize more on Boro season to feed more people. That’s why forty entries of Boro rice germplasm were allowed to evaluate for their genetic variations in yield and yield contributing traits, their associations and also direct and indirect effects on yield. Observing means, range and all genetic parameters, selection could be done on the basis of number of effective tillers, harvest index, filled grains per panicle, unfilled grains per panicle, days to maturity and grain yield. Traits association analysis revealed that days to flowering, days to maturity and filled grain per panicle could significantly improve rice germplasm. Path analysis estimated that direct selection based on days to flowering, days to maturity and filled grain per panicle would be efficient for improvement of rice germplasm. G5 had the highest yield along with filled grain per plant, harvest index and 1000 grain weight and it could be used as potential variety for improving yield. The germplasm G7, G19, G9 and G33 could be used in further breeding program for the improvement of rice germplasm.SAARC J. Agri., 17(2): 103-115 (2019)